Estructuras comerciales romanas en el período pre-anibálico: una lectura crítica interdisciplinar del período medio repúblicano - Domínguez Pérez, Juan Carlos (Gerión. Revista de Historia Antigua, 2006)
Traditionally we have considered that Rome, during the Mid-Republican age, had no structures to develop a market rule in the Mediterranean Sea. In this paper we try to analyse the remains the submarine archaeology has provided in the last years, so much as the recent campaigns in the religious area of San Omobono, in the just Rome, and we do it from a critical point of view and in relation to the reticular structure of “ports of trade” that Rome had performed in its maritime politics long before Anibal turned up in its historical outlook.